PENGARUH HARGA DAN KUALITAS PRODUK TERHADAPMINAT BELI KONSUMEN AMDK MEREK AQUA (STUDI KASUS DI KOTA SERANG): PENGARUH HARGA DAN KUALITAS PRODUK TERHADAPMINAT BELI KONSUMEN AMDK MEREK AQUA (STUDI KASUS DI KOTA SERANG) (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the effect of price and product qualitysimultaneously on consumer buying interest in Aqua brand bottled water. This type of researchis descriptive analytic, with data collection techniques through questionnaires. The samplingtechnique uses non-probability, the sample is100 people who are consumers who are buying Aqua Brand AMDK products at the Alfamart orIndomart minimarkets, Cipocok District. The analytical method used in this research isquantitative data analysis.The results of the descriptive analysis of respondents revealed that the majority of respondentswere 21-30 years old (51%), female (63%), and the last education was PT (72%). From theresults of hypothesis testing, it shows that the price variable (p=0.004) and product quality(p=0.000) have a positive and significant effect on consumer buying interest. And together thevariables of product quality and price have a positive and significant effect (p = 0.000) onconsumer buying interest. Then the contribution of product quality and price variables toconsumer buying interest is 62.2%. The remaining 37.8% is influenced by other factors that arenot in this study. The conclusion of this study is the price and product quality have a positiveand significant effect on consumer buying interest in Aqua brand bottled water either partiallyor simultaneously.